State regulation of the financial market in accordance with modern trends of financial globalization. (Journal of Economic Research & Business Administration, 2015)
The article to correct methodological positions discussed the role and features of state regulation of the financial market. The study in the article is particularly relevant issues in the post-crisis period. Attention is paid to the state regulation of the financial market in the conditions of financial globalization. Also highlighted the main stages and development of the market model in the Republic of Kazakhstan.